A study of outcome of diaphyseal fractures of radius and ulna in paediatric age group treated with titanium elastic nailing system - Bedge, Vijayanand; M. V., Rakesh; B., Darshan; Belaval, Naveen M. (International Journal of Research in Orthopaedics, 2024)
A study of outcome of diaphyseal fractures of radius and ulna in paediatric age group treated with titanium elastic nailing system. The current study is an attempt to find out the functional outcome, radiological union, and complications of paediatric diaphyseal radius and ulna fracture treated with titanium elastic nail. This is a prospective study of twenty-five patients of age group 6 years to 16 years diagnosed with a diaphyseal fracture of radius and ulna treated with percutaneous nailing with titanium elastic nails in Department of Orthopaedics, S Nijalingappa Medical College and HSK Hospital, Bagalkot between November 2019 to April 2022. Clinical, functional and radiological outcomes were assessed with Anderson et al criteria for 6 months. In terms of union and range of motion using Anderson et al criteria 20 patients had excellent results, 2 patients had satisfactory results and one patient had an unsatisfactory result. There were no cases of poor results. Five cases had complications like Nail prominence, elbow stiffness, olecranon bursitis and super skin infection. The radiological union was achieved in a mean time of 8.24±2.62 weeks. Complications resolved after implant removal. Titanium elastic nail system showed excellent results in terms of bony union, functional outcome with minimal complications which resolve after nail exit. Therefore, titanium elastic nail system should be considered as an effective alternative of conservative management for forearm fractures in pediatric age group.